Ancestral Landscapes of the Pueblo World - Snead, James E. (James Elliott), 1962-; Project Muse. (Tucson : University of Arizona Press, 2008)
"The eastern Pueblo heartland, located in the northern Rio Grande country of New Mexico, has fascinated archaeologists since the 1870s. In Ancestral Landscapes of the Pueblo World, James Snead uses an exciting new approach - landscape archaeology - to understand ancestral Pueblo communities and the way the people consciously or unconsciously shaped the land around them. Snead provides detailed insight into ancestral Puebloan cultures and societies using an approach he calls "contextual experience," employing deep mapping and community-scale analysis. This strategy goes far beyond the standard archaeological ethnography and contemporary Puebloan perspectives to better understand how past and present Pueblo worldviews and meanings are imbedded in the land." "Snead focuses on five communities in the Pueblo heartland - Burnt Corn, Tobimpaenge, Tsikwaiye, Los Aguajes, and Tsankawi - using the results of intensive archaeological surveys to discuss the changes that occurred in these communities between AD 1250 and 1500. He examines the history of each area, comparing and contrasting them via the themes of "provision," "identity," and "movement," before turning to questions regarding social, political, and economic organization. This revolutionary study thus makes an important contribution to landscape archaeology and explains how the Precolumbian Pueblo landscape was formed."--BOOK JACKET.
Landscapes -- Histories -- Provision -- Identity -- Movement -- Competition.
Description based on print version record.
Keywords: Social archaeology; Pueblo Indians -- Land tenure; Pueblo Indians -- Antiquities; Landscape archaeology; Excavations (Archaeology); Antiquities; Excavations (Archaeology) -- Rio Grande Valley (Colo.-Mexico and Tex.); Social archaeology -- Rio Grande Valley (Colo.-Mexico and Tex.); Landscape archaeology -- Rio Grande Valley (Colo.-Mexico and Tex.); Pueblo Indians -- Rio Grande Valley (Colo.-Mexico and Tex.) -- Antiquities; Pueblo Indians -- Land tenure -- Rio Grande Valley (Colo.-Mexico and Tex.); North America -- Rio Grande Valley; Rio Grande Valley (Colo.-Mexico and Tex.) -- Antiquities; Electronic books